Antenatal exposure to antidepressants is associated with altered brain development in very preterm-born neonates. (7th February 2017) - Podrebarac, Samantha K.; Duerden, Emma G.; Chau, Vann; Grunau, Ruth E.; Synnes, Anne; Oberlander, Tim F.; Miller, Steven P.
Highlights: Antidepressants are associated with a risk of preterm birth. Effect of antenatal exposure on preterm brain development remains unknown. Preterm newborns exposed to antidepressants in utero had impaired brain maturation. The mechanism of this relationship needs to be determined. Treatment for depression in mothers at risk for preterm delivery needs attention. Abstract: Background: Antenatal exposure to selective serotonin reuptake inhibitors (SSRIs) is associated with an enhanced risk of preterm birth. Very preterm-born neonates (<32 weeks' gestation) antenatally-exposed to SSRIs may show altered brain development. Objective: To examine whether antenatal-SSRI exposure was associated with adverse neonatal brain microstructural and metabolic development using diffusion tensor and magnetic resonance spectroscopic imaging. Design/Methods: Of 177 neonates enrolled, 14 (8%) were antenatally exposed to SSRIs. Neonates were scanned twice (median week 32; interquartile range [IQR]: 30.4–33.6) and again at term-equivalent age (40.1, IQR: 38.6–42.1). Using a region-of-interest approach, N-acetylaspartate to choline ratios (NAA/Cho), lactate to choline ratios, white and gray matter fractional anisotropy (FA), mean, axial, radial diffusivity (MD, AD, RD) values were extracted from white and gray matter subcortical regions. Neurodevelopment was assessed at 18 months, corrected age. Results: SSRI-exposed neonates exhibited increased FA and decreased MD, AD and RD values in the superior white matter ( p  < 0.05). FA values in the basal ganglia and thalamus were significantly lower in neonates antenatally exposed to SSRIs, compared to non-exposed ( p  = 0.004). Lower NAA/Cho values ( p  = 0.04) and higher Lactate/Cho values ( p  = 0.004) in posterior gray matter were evident in neonates exposed to SSRIs. No association with antenatal-SSRI exposure and neurodevelopment was evident. Conclusions: Given the importance of treating depression in mothers at risk for preterm delivery, the impact of antenatal-SSRIs on early brain development requires further attention. Future research is directed at determining the mechanism of this relationship and the contribution of maternal mood.